Experimental Study on Tunnel Failure Mechanism and the Effect of Combined Anti-Dislocation Measures Under Fault Dislocation - Jiaxuan Du; Songhong Yan; Weiyu Sun; Mingxing Cao; Yuxiang Li (Applied Sciences)
Taking the tunnels crossing active faults in China’s Sichuan–Tibet Railway as the research background, experimental studies were conducted using a custom-developed split model box. The research focused on the cracking characteristics of the surrounding rock surface under the action of strike-slip faults, the progressive failure process of the tunnel model, and the mechanical response of the tunnel lining. In-depth analyses were performed on the tunnel damage mechanism under strike-slip fault action and the mitigation effects of combined anti-dislocation measures. The results indicate the following: Damage to the upper surface of the surrounding rock primarily occurs within the fault fracture zone. The split model box enables the graded transfer of fault displacement within this zone, improving the boundary conditions for the model test. Under a 50 mm fault displacement, the continuous tunnel experiences severe damage, leading to a complete loss of function. The damage is mainly characterized by circumferential shear and is concentrated within the fault fracture zone. The zone 20 cm to 30 cm on both sides of the fault plane is the primary area influenced by tunnel forces. The force distribution on the left and right sidewalls of the lining exhibits an anti-symmetric pattern across the fault plane. The left side wall is extruded by surrounding rock in the moving block, while the right side wall experiences extrusion from the surrounding rock in the fracture zone, and there is a phenomenon of dehollowing and loosening of the surrounding rock on both sides of the fault plane; the combination of anti-dislocation measures significantly enhances the tunnel’s stress state, reducing peak axial strain by 93% compared to a continuous tunnel. Furthermore, the extent and severity of tunnel damage are greatly diminished. The primary cause of lining segment damage is circumferential stress, with the main damage characterized by tensile cracking on both the inner and outer surfaces of the lining along the tunnel’s axial direction.